Early response genes in the pathogenesis of cancer of the cervix uteri: a review - O. V. Kurmyshkina; T. O. Volkova; P. I. Kovchur; I. E. Bakhlayev; N. N. Nemova (Опухоли женской репродуктивной системы, 2014)
Early response genes are a group of proto-oncogenes that are the first to be activated in cell stimulation with different growth factors and to be involved in the regulation of cell proliferation and differentiation. Large amount of information supporting that altered expression of these genes is one of the central and earliest events of carcinogenesis has been accumulated. In this connection, it is promising to use early response genes as diagnostic and prognostic markers for the detection and combination therapy of cancer of the cervix uteri, one of the most common gynecological malignancies characterized by high mortality rates and difficulties in early diagnosis. The theoretical basis for these promises is the found mechanisms for the interaction of early response genes with human papillomavirus genome, the main cause of cervix uteri cancer.